Assessment of Food Security, Anthropometric and Cognitive Function among Orang Asli Children in Pahang, Malaysia - Teh, S.C.; A., Asma’; Hamid Jan, J.M.; Yusof, H.M. (IIUM Medical Journal Malaysia, 2020)
Introduction: Forest clearing for agriculture plantations and local community settlements may trigger food insecurity, which causes poor development, predominantly in Orang Asli children. This cross-sectional study was conducted to determine the relationships between food security and anthropometric and cognitive function among Orang Asli children in Temerloh, Pahang. Materials and methods: A total of one hundred and sixty-seven children (ages 7 to 11) from five selected Orang Asli villages (Kampung Sungai Enggang, Kampung Penderas, Kampung Pasu, Kampung Lubok Wong, and Kampung Pian) were involved in this study. The food security index was assessed using the Radimer/Cornell Hunger and Food Insecurity Instrument. Anthropometric indices were based on height-for-age and BMI-for-age Z-scores, while cognitive performance was tested using Raven’s Coloured Progressive Matrices (R-CPM). Results: A majority (91.6%) of the respondents reported some kind of food insecurity (12.6% household food insecure, 74.2% individual food insecure, and 4.8% child hunger). Rates of stunting, thinness, and overweight/obesity were 25.8%, 16.2%, and 18.0%, respectively. A majority (46.1%) of the children had average cognitive scores, followed by below average (38.3%) and above average (15.6%), respectively. Height-for-age was significantly associated with cognitive function (p=0.008). Among sociodemographic factors, household size (p=0.007) and household income (p<0.05) were significantly associated with the food security index, whereas the educational status of the child was significantly associated with height-for-age (p=0.013) and cognitive function (p=0.003). Conclusion: Food insecurity remains a risk factor for child development impairment in the Orang Asli community. Undernutrition remains a major health concern among respondents; however, no association was found between food security index and cognitive function.